Self-Efficacy and Study Habits on Mathematics Knowledge of Fifth Grade Elementary School Students - Ni Kadek Ayu Dwi Widia Rini; Gusti Ngurah Sastra Agustika (Universitas Pendidikan Ganesha, 2023)
The achievement of the fifth grade students' mathematical knowledge is relatively low. Internal factors and external factors are the causes of low student learning outcomes. This study aims to analyze self-efficacy and study habits on the Mathematics knowledge of fifth grade elementary school students. This study uses an ex post facto research design with a correlational study approach. The population in this study were all 197 students of class V elementary school. The sample in this study was determined using a proportional random sampling technique with a total sample of 132 people. The method in this study uses non-test methods, namely questionnaires and document recording. Analysis of research data using simple linear regression analysis and multiple linear regression analysis. The results of the research analysis show that based on the correlation coefficient test at a significance level of 5% with dk = 130, rtable = 0.171, thus rcount = 0.831 > rtable = 0.171, which means the coefficient value is significant. Furthermore, the coefficient of determination obtained was R2 = 0.691 and its contribution was 69.1% of the variation in Mathematics knowledge scores determined by self-efficacy and study habits. Based on these results, it can be concluded that there is a significant joint influence of self-efficacy and study habits on Mathematics knowledge. 1% of the variation in Mathematics knowledge scores is determined by self-efficacy and study habits. Based on these results, it can be concluded that there is a significant joint influence of self-efficacy and study habits on Mathematics knowledge. 1% of the variation in Mathematics knowledge scores is determined by self-efficacy and study habits. Based on these results, it can be concluded that there is a significant joint influence of self-efficacy and study habits on Mathematics knowledge.